Learning to Write Like a Scientist: A Writing-Intensive Course for Microbiology/Health Science Students - Kimi Grzyb (American Society for Microbiology, 2018)
Learning the tools and conventions of expert communication in the sciences provides multiple benefits to bioscience students, yet often these skills are not formally taught. To address this need, we designed a writing-intensive microbiology course on emerging infectious diseases to provide upper-division students with science-specific writing skills along with disciplinary course content. The course followed the guidelines of our university’s Writing Intensive Curriculum (WIC) program. Students wrote a press release, a case study, a controversy/position paper, and a grant prospectus, and revised drafts after feedback. To assess the course, in 2015 and 2016 we administered pre-post surveys and collected writing samples for analysis. Students reported on their experience, training, skills, and knowledge before taking the course. They then rated the extent to which the assignments, lectures, in-class activities, and writing activities contributed to their attainment of the learning outcomes of the course. Students entering the class were inexperienced in tools of science writing and the specific genres covered by the class. Their confidence levels rose in both skills and knowledge. Feedback from instructors was cited as most helpful in the majority of the areas where students reported the most gains. The survey provided evidence that discipline-specific knowledge had been acquired through writing activities. Teaching science writing by allowing the students to write “fiction” (e.g., a case report about a fictional patient) was effective in maintaining a high level of interest, both in learning the conventions of the genre and in seeking out detailed information about emerging infectious diseases. Both the course structure and the specific assignments would be useful at other institutions to teach science writing.